Marital rehabilitation after prostate cancer – a matter of intimacy. Issue 1 (18th August 2015) - Dieperink, Karin B.; Mark, Karen; Mikkelsen, Tina Broby
ABSTRACT: Prostate cancer is the most frequent male cancer disease in the western world. Sexual dysfunction is common after prostate cancer with radiation therapy and androgen deprivation therapy, but further research is needed to determine the lived experience of couples struggling with sexual dysfunction after treatment. The purpose of this study was to explore the lived experience of men and their partners experiencing sexual side effects after radiation therapy and androgen deprivation therapy for prostate cancer. In addition, to understand the role of a structured rehabilitation program on the couple's experience. Couples with persistent sexual problems were recruited among patients treated with radiotherapy or/and androgen deprivation therapy. Descriptive statistics were collected including age, race, education and work. Focus groups with each gender were conducted using open ended questions to encourage participants to talk about their experiences. Data were analyzed using Giorgi's phenomenological method. A total of eight couples were recruited, men age 67 years [standard deviation (SD) 6·3], women 65 years (SD 7·2). Results from the focus group interviews regarding marital relations were grouped in three themes: negative impact of sexual dysfunction on the relationship; other physical and psychological consequences of late adverse effects; communication issues and partner feelings of frustration. Results regarding the rehabilitation program were grouped in four themes: importance of peer support; importance of time and space for reflection; improved communication; optimism after rehabilitation. The couples in this study reported that the sexual side effects of prostate cancer treatment impacted their relationship and were problematic for both the men and their partners. The rehabilitation program improved the couples communication concerning sexual intimacy and issues related to prostate cancer treatment. It also offered a chance for peer support from others going through similar experiences and increased hope for navigating through sexual and intimacy issues in the future.